2006
DOI: 10.1001/jama.295.18.2148
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Collaborative Care for Older Adults With Alzheimer Disease in Primary Care

Abstract: clinicaltrials.gov Identifier: NCT00246896.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
838
2
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 693 publications
(862 citation statements)
references
References 51 publications
12
838
2
10
Order By: Relevance
“…229 In this approach a care/case manager co-ordinates care between professionals, liaises between primary and secondary care and utilises evidence-based care pathways to address both physical and psychosocial needs. Despite positive benefits for both PLWD and their carers in some individual trials, 230 recent systematic reviews have found little clinical effectiveness or cost-effectiveness evidence to support widespread case management implementation beyond some quality-of-life benefits. 186,188,189 A recent pilot trial to evaluate the feasibility of case management in the UK struggled to successfully implement a nurse/social worker case manager intervention despite considerable support for this care approach from both patients and primary care teams.…”
Section: Holistic Carementioning
confidence: 99%
“…229 In this approach a care/case manager co-ordinates care between professionals, liaises between primary and secondary care and utilises evidence-based care pathways to address both physical and psychosocial needs. Despite positive benefits for both PLWD and their carers in some individual trials, 230 recent systematic reviews have found little clinical effectiveness or cost-effectiveness evidence to support widespread case management implementation beyond some quality-of-life benefits. 186,188,189 A recent pilot trial to evaluate the feasibility of case management in the UK struggled to successfully implement a nurse/social worker case manager intervention despite considerable support for this care approach from both patients and primary care teams.…”
Section: Holistic Carementioning
confidence: 99%
“…A more recent study demonstrated that a training and support intervention delivered to nursing home staff decreased the use of antipsychotics (Fossey et al, 2006). Additionally, collaborative care management in primary care settings, when compared with augmented usual care, showed improvements in overall severity of neuropsychiatric symptoms (Callahan et al, 2006). Thus, possible problems in dissemination and implementation should not stand in the way of carrying out methodologically sound RCTs of nonpharmacological interventions in patients with dementia.…”
Section: Psychosocial and Psychotherapeutic Interventionsmentioning
confidence: 99%
“…1,3 These challenges may be addressed through the recent development of interprofessional and collaborative care approaches to dementia within the primary care setting. 33 The Primary Care Collaborative Memory Clinic model in which family physician-led memory clinics are embedded in group practice settings provides comprehensive assessment and recommendations for management and continuing shared care with the patient's own Practice improvements were related to improved screening and assessment, particularly as related to the use of the brain map to better differentiate types of dementia, improved recognition of delirium and improved prescribing.…”
Section: Family Medicine Original Articlesmentioning
confidence: 99%